Neurobiology of chronic caffeine use and withdrawal : Mechanisms, effects and implications - Yu Zhao, Lee; Ker Ni, Chua; Fui Ling, Voon; Chau Ling, Tham; Yu Cheng, Ho; Ming Tatt, Lee (Elsevier Ltd., 2026)
Caffeine is the most widely consumed psychoactive substance worldwide and is increasingly being explored for its potential pharmacological applications, including in neurodegenerative diseases, cognitive enhancement, and pain modulation. However, chronic caffeine use leads to neuroadaptive changes that underlie dependence and a well-characterized withdrawal syndrome, which includes symptoms such as headache, fatigue, cognitive impairment, and mood disturbances. This review critically examines the neurobiology of chronic caffeine exposure and withdrawal, focusing on its interaction with adenosine receptor systems, neural plasticity, and the role of genetic and time-course variability in modulating individual responses. Evidence from human and animal studies is discussed to highlight mechanisms driving tolerance, sensitisation, and withdrawal symptoms. We further discuss the broader implications for public health and society, particularly in relation to substance use patterns, cessation strategies, and the safe integration of caffeine into therapeutic applications. As caffeine continues to be investigated as a therapeutic agent, understanding its dependence potential and withdrawal effects is essential to ensure safe and effective clinical applications. This paper underscores the importance of integrating neurobiological, behavioural, and genetic insights to fully evaluate the implications of long-term caffeine consumption.